External influences: “Hellenization”, “Romanization”, “Mediterraneization” (6th - 3rd cent. BCE) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2020)
The introduction of writing in Western Mediterranean is an important step in the historical process of acculturation, bringing about a relevant impact on the previous oral literary tradition. In the Iberian peninsula, the heterogeneous documentation and its difficult interpretation prevent the authors from deepening the research. The interconnection of the diverse writing system between the 6th and 3rd c. BCE is presented, with reference to their Phoenician and Greek counterparts. The Latin and Etrusco-Italic epigraphy of production provides a case-study, which prove the steady relationship of craftsmen with writing. In Etruria, the shift of the standard gift-formulas from the ritual aristocratic to the votive ambit occurs in the framework of the frequentation of foreign visitors.